Improving program comprehension by automatic metamodel abstraction - Vagac, Michal; Kollár, Ján (Computer Science and Information Systems, 2012)
The maintenance of a software system represents an important part in its lifetime. In general, each software system is the subject of different kinds of changes. Bug fixes and a new functionality extensions are the most common reasons for a change. Usually, a change is accomplished by source code modifications. To make such a modification, correct understanding the current state of a system is required. This paper presents the innovative approach to the simplification of program comprehension. Based on the presented method, the affected software system is analyzed and metamodel for the selected feature is created. The feature represents functional aspect of a system being the subject of the analysis and change. The main benefit is that by focusing on well known (and precisely described) parts of program implementation, it is possible to create metamodel for implementation parts automatically. The level of metamodel is at a higher level of abstraction than implementation. nema